2020
DOI: 10.1111/eip.12992
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric comorbidity in individuals at‐risk for psychosis: Relationships with symptoms, cognition and psychosocial functioning

Abstract: Aim: Psychiatric comorbidity frequently occurs with at-risk mental state (ARMS) for psychosis. Its relationships with psychopathology, cognition and functioning, however, remain to be further clarified. We aimed to examine prevalence and correlates of psychiatric comorbidity, and its associations with psychosocial functioning and subjective quality-of-life (QoL) in a representative sample of Chinese ARMS individuals.Methods: One hundred ten help-seeking participants aged 15 to 40 years with ARMS were recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Therefore, it might not be cavalier to suggest that a portion of these subjects might already have 'asymptomatic disease' (or preperimetric glaucoma) (Figure 3), and this damage was undetectable on stereoscopic photography, which was also suggested by Weinreb et al [11]. The ever-evolving OCT technology and the concepts of ONH assessment can provide valuable data and new parameters for further refinement of the existing risk calculator, for instance, integrating other factors of OHN and RNFL based on OCT measurement [22]. The glaucoma risk model needs refinement that involves the advancing OCT technologies and concepts in measuring VCDR.…”
Section: Detection Of Retinal Nerve Fibre Layer Defect and Early Diagmentioning
confidence: 84%
See 4 more Smart Citations
“…Therefore, it might not be cavalier to suggest that a portion of these subjects might already have 'asymptomatic disease' (or preperimetric glaucoma) (Figure 3), and this damage was undetectable on stereoscopic photography, which was also suggested by Weinreb et al [11]. The ever-evolving OCT technology and the concepts of ONH assessment can provide valuable data and new parameters for further refinement of the existing risk calculator, for instance, integrating other factors of OHN and RNFL based on OCT measurement [22]. The glaucoma risk model needs refinement that involves the advancing OCT technologies and concepts in measuring VCDR.…”
Section: Detection Of Retinal Nerve Fibre Layer Defect and Early Diagmentioning
confidence: 84%
“…The study showed that there was disagreement in VCDR measurements between the three methods. This disagreement also extended to their corresponding 5-year risk estimation of POAG development [22]. When the comparison was made on the Bland-Altman plots, the range of discrepancies tended to widen with increasing mean risk, especially beyond the estimated Figure 2.…”
Section: Variability Of Risk Factor Measurement and The Effects On Rimentioning
confidence: 95%
See 3 more Smart Citations